Tuan Desa Application Menggunakan Metode Topsis Sebagai Penentuan Rencana Kerja Pembangunan Desa - Prasetyo, Muhamad Awiet Wiedanto (JST (Jurnal Sains dan Teknologi), 2022)
It has been empathized that village funds are prioritized to finance the implementation of village-scale programs and activities in the field of village development and village empowerment. The village government is still making decisions by way of deliberation with village communities in the absence of definite aspects that can be taken into consideration. From the deliberation results are often not accepted because they do not see the needs that can be utilized more by the community, this is the main problem in the preparation of work program activities or budgets every year. It begins with conducting interviews with village officials, followes by observing the process of deliberation activities at the neighborhood level, hamlet meetings and ending with village meetings the looking for references in the form of literature in the form of research journals with the theme of website application, making protorypes of the RKPDes application, calculating TOPSIS method, and producsing RKPDes preparation websote application. The conclusion of this study is that the TOPSIS method can adjust the process of compiling the neighborhood council, hamlet and village meetings to prepare the RKPDes.